-n+7(n-4)=-2(5n-2)

Simple and best practice solution for -n+7(n-4)=-2(5n-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -n+7(n-4)=-2(5n-2) equation:


Simplifying
-1n + 7(n + -4) = -2(5n + -2)

Reorder the terms:
-1n + 7(-4 + n) = -2(5n + -2)
-1n + (-4 * 7 + n * 7) = -2(5n + -2)
-1n + (-28 + 7n) = -2(5n + -2)

Reorder the terms:
-28 + -1n + 7n = -2(5n + -2)

Combine like terms: -1n + 7n = 6n
-28 + 6n = -2(5n + -2)

Reorder the terms:
-28 + 6n = -2(-2 + 5n)
-28 + 6n = (-2 * -2 + 5n * -2)
-28 + 6n = (4 + -10n)

Solving
-28 + 6n = 4 + -10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10n' to each side of the equation.
-28 + 6n + 10n = 4 + -10n + 10n

Combine like terms: 6n + 10n = 16n
-28 + 16n = 4 + -10n + 10n

Combine like terms: -10n + 10n = 0
-28 + 16n = 4 + 0
-28 + 16n = 4

Add '28' to each side of the equation.
-28 + 28 + 16n = 4 + 28

Combine like terms: -28 + 28 = 0
0 + 16n = 4 + 28
16n = 4 + 28

Combine like terms: 4 + 28 = 32
16n = 32

Divide each side by '16'.
n = 2

Simplifying
n = 2

See similar equations:

| x^3+7x^2+2x=0 | | -x^2+x+56=0 | | 40+14j=2(-4j+-13) | | -6h+2h-11=-2(2h-3)+4 | | x=.5(3+7)4 | | p/5=6 | | -6x+3y=-30 | | -37+2m=-7(-m+1) | | -x^2+21+x=0 | | -5+2x=-1 | | 2n-6=-24 | | 28x^2-37x-21= | | 3(4c+1)-17=2(3c+2)-3c | | 5=7x-2 | | (7.29)(0.6+0.7)= | | 3(2x+1)=5 | | 7x-5y=-19 | | -3x+6=-27 | | y=0.3-2 | | (3w+5)(3w-5)= | | .5x+.40(400)=.10(x+400) | | 2x(-10)+y(-11)=180 | | -3x+6=-24 | | .5x+.30(400)=.10(x+400) | | -5x+8=-7 | | -8x^2-39x+5=0 | | 2x-10+y-11=180 | | 64+27=97+x | | 6-7(a+1)-7x=6+5x-2 | | 4x+2y=43 | | 8x-10=22+4x | | 14+x=2-2x |

Equations solver categories